2021
DOI: 10.1155/2021/9959779
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Gestational Diabetes and Anxiety or Depression: A Systematic Review

Abstract: Gestational diabetes mellitus (GDM) pregnant women are under more psychological stress than normal pregnant women. With the deepening of the study of gestational diabetes mellitus, research has shown that anxiety and depression are also an important cause of gestational diabetes mellitus. Anxiety and depression can cause imbalances in the hormone levels in the body, which has a serious impact on the pregnancy outcome and blood glucose control of pregnant women with GDM. Therefore, the main purpose of this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(49 citation statements)
references
References 55 publications
0
48
0
1
Order By: Relevance
“…Gestational diabetes mellitus (GDM) is the most common metabolic complication during pregnancy, affecting up to 25% of pregnancies [ 1 ]. Women with GDM have higher risks of developing hypertensive disorders during pregnancy, in particular, pre-eclampsia, pre-term birth, cesarean delivery, as well as mental health problems such as anxiety and depression [ 2 , 3 , 4 ]. Risks to the children include macrosomia (20–30%), small for gestational age (7–10%), shoulder dystocia, neonatal hypoglycemia, neonatal hyperbilirubinemia, respiratory distress syndrome and stillbirth [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gestational diabetes mellitus (GDM) is the most common metabolic complication during pregnancy, affecting up to 25% of pregnancies [ 1 ]. Women with GDM have higher risks of developing hypertensive disorders during pregnancy, in particular, pre-eclampsia, pre-term birth, cesarean delivery, as well as mental health problems such as anxiety and depression [ 2 , 3 , 4 ]. Risks to the children include macrosomia (20–30%), small for gestational age (7–10%), shoulder dystocia, neonatal hypoglycemia, neonatal hyperbilirubinemia, respiratory distress syndrome and stillbirth [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…More studies involving vulnerable populations are required to better understand how structural features of perinatal interventions impact the prevention of pregnancy issues such as GDM. Additionally, studies have identified stress and anxiety as potential risk factors for GDM [ 50 , 51 , 52 ]. The large majority of participants in the present study had a low household income and were therefore more likely to present high stress and anxiety levels related to economic precarity.…”
Section: Discussionmentioning
confidence: 99%
“…In studies on murine prenatal stress, males’ placental OGT and O -GlcNAcylation levels were more impacted than females. With extra copies of OGT available, it was hypothesized that female offspring may have a greater capacity to rapidly respond to maternal stress 29 or, in the case of gestational diabetes, prolonged exposure to hyperglycemic stress 4548 . In this context, we hypothesized that male placental OGT and O -GlcNAcylation levels might be more affected by stressors leading to induction of GDM.…”
Section: Discussionmentioning
confidence: 99%